Magnetic microsphere based droplet microarray for high-throughput screening of multiple chemical residues in milk - Liu, Chen; Zhai, Peng; Luo, Pengjie; Zhang, Huiya; Zou, Boyu; Liao, Meiting; Jiang, Wenxiao (Food chemistry, 2025)
In this paper, aflatoxin M1, sulfamethoxazole, ciprofloxacin, and lincomycin were selected as model analytes, and we introduced a novel quadplex droplet microarray format for simultaneous screening of multiple chemical residues in milk samples. The droplet microarray relied on micro-volume shallow-well microplate combined with microspheres-based suspension array. In the new established droplet microarrays, the consumption of samples and immunoreagents was reduced by 80 %. While, the antigen-antibody binding process can be completed in as little as 5 min. The limit of detection was evaluated to be 0.023 μg/kg for aflatoxin M1, 5.68 μg/kg for sulfamethoxazole, 0.85 μg/kg for ciprofloxacin, and 2.65 μg/kg for lincomycin. The recoveries of the target analytes from spiked milk were 79.7 %–102.6 %, with the coefficients of variation not larger than 10.6 %. The newly developed droplet microarray has been demonstrated with good validity and sensitivity by comparing it with the conventional immunoassays and instrumental methods. •A micro-volume shallow-well microplate was fabricated for new immunoassay development.•A quadplex droplet microarray was developed for screening of multiple chemical residues in milk.•The sample usage and the consumption of immuno-reagents could be reduced by 80 %.•The antigen-antibody binding process can be completed within 5 min.•The developed assay format could be expanded to other chemical analysis.